Prussian‐Blue Catalysis and NFC Synergy: a Battery‐Free Laser‐Induced Graphene‐Based Platform for Urine Glucose Monitoring at Point‐of‐Care - Uzunçar, Sinan (2025)
Prussian-blue nanoparticles (PBNPs) show promise in electrochemical hydrogen peroxide (H2O2) sensing but face operational stability challenges without complex strategies. This study introduces a simplified, polymer-based synthesis method, enhancing their stability in a single step. Chemical polymerization of Prussian-blue (PB) and poly(3,4-ethylenedioxythiophene) (PEDOT) with gelatin as a polycationic soft template yields a self-assembled PB-infused Catalytic Hetero-interface Architecture (PB-CHIA) that remarkably improves the stability of PBNPs and offers functional groups for enzyme immobilization, supporting robust biosensing applications. The softened PEDOT rigidity extends PB-CHIA´s applicability to various carbonaceous electrode substrates, including glassy carbon and laser-induced graphene (LIG) via simple drop-casting. A fluidic cell module designed with the optimized LIG morphology (nano-fibrous fringes, LIG-F, diameter: 72.87 ± 12.24 nm) modified with PB-CHIA and glucose oxidase enables non-invasive urine glucose monitoring. The configuration accurately quantifies glucose within a linear range of 10–400 µM [R2: 0.991, Sensitivity: 29.88 ± 4.98 µA mM⁻¹ cm⁻2, Detection Limit: 4.52 ± 2.24 µM], covering medical needs. A near-field communication potentiostat is devised for a fully integrated, batteryless, wireless point-of-care (POC) prototype, enabling rapid smartphone readouts in 15 s for daily home-based use. The stable operation of PB-CHIA allows working electrodes’ scalable production, highlighting its potential for diverse POC devices in urinary analysis reliant on H2O2 assays.